Castleman's Disease : Clinicopathological Characteristics of a Cohort of Hispanic Patients - Montante-Montes, Daniel; Lizardo-Thiebaud, María José; Rodriguez-Rodriguez, Sergio; Monroy-Ramos, Cinthya; Riveros Gilardi, Berta; Seidman-Sorsby, Alec; García Carrera, Isabel; Sandoval López, José de Jesús; Aguayo, Alvaro; Martínez-Baños, Déborah (My University, 2022)
Introduction: Castleman Disease (CD) depicts a group of heterogeneous hematologic disorders with characteristic histopathological features. Two forms of CD are recognized,unicentric (UCD) or multicentric (MCD). This classification relies on the number of regions of lymph node involvement. Objetives: To describe the clinicopathological characteristics of a cohort of Hispanic patients with Castleman's Disease. Material: Patients with CD diagnosis that were followed at the Monoclonal Gammopathies Clinic in INCMNSZ, from January 2006 to July 2022 were included.A team of pathologists that included a trained hematopathologist reviewed the biopsies, extended the immunohistochemical panel and classified the cases according to the International, evidence-based consensus diagnostic criteria for HHV8 negative/idiopathic MCD. ©The aurhors.